2020
DOI: 10.3390/rs12233963
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Devices and GNSS Collars with Satellite Communication to Detect Calving Events in Extensive Beef Production in Northern Australia

Abstract: Observing calves at birth may help to identify risk factors for, and reduce, calf loss in extensive beef systems. The objectives of this study were to: (1) evaluate two commercial satellite birth alert systems to enable the observation of newborn calves and (2) assess behavioral changes of cows around calving. Vaginal Implant Transmitters (VIT) paired with Global Navigation Satellite System (GNSS) collars were worn by 20 cows in Trial 1 and 10 cows in Trial 2 to identify birthing events. The VIT and GNSS colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Prolonged periods of inactivity combined with a change in temperature larger than the expected biological variation in body temperature was Tail position score from 0 to 8 h after e-Synch device insertion for cows in experiment 2. Ren et al 10.3389/fanim.2023.1093851 proposed as a method for detection of expulsion of intravaginal devices during calving in cattle (Pearson et al, 2020). Cow position data from the accelerometer could be used to prevent backflow from the vagina by releasing fluid only when cows are standing.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged periods of inactivity combined with a change in temperature larger than the expected biological variation in body temperature was Tail position score from 0 to 8 h after e-Synch device insertion for cows in experiment 2. Ren et al 10.3389/fanim.2023.1093851 proposed as a method for detection of expulsion of intravaginal devices during calving in cattle (Pearson et al, 2020). Cow position data from the accelerometer could be used to prevent backflow from the vagina by releasing fluid only when cows are standing.…”
Section: Discussionmentioning
confidence: 99%
“…Correct identification of calving was reached in 66% of deliveries while localization of animals was achieved in 64% of cases with an approximation of 100-200 m. Tracking parturient animals in extensive grazing areas is a concern in Australian breeding systems. Placing radio receiving antennae could be difficult due to the ground topography; thus researchers are also evaluating a Vaginal Implant Transmitter (VIT) device which is equipped with temperature and accelerometer sensors coupled to a GNSS collar for tracking via satellite technology [101]. The device is still a prototype at present, and more improvement is needed for field use.…”
Section: Intravaginal Devicesmentioning
confidence: 99%
“…For example, GNSS-enabled collars have been used to track and monitor livestock behavior in grazinglands for some time [30,31,33,[85][86][87][88]. Distinguishing resting and foraging behaviors [30,[89][90][91][92], distance traveled to/from water [33,93], seeking out high quality forage [31,90], terrain/topographical preferences/avoidance [32,93], response to disturbance and environmental stressors [94][95][96], birth detection [97], and circadian rhythms [98] have all been studied through GNSS tracking collars and accelerometers.…”
Section: Field Data Integrationmentioning
confidence: 99%
“…These authors differentiate between grazing, standing, walking, and lying with up to 10-s moving window durations. Pearson et al [97] outfitted cattle with GNSS collars and intravaginal devices to test the ability to detect birthing events, and potential behavioral changes due to birthing. They found that birth detection in these systems were lacking, most likely due to the length of time the devices must remain implanted.…”
Section: New Management Applicationsmentioning
confidence: 99%